A Situational Analysis of Early Childhood Development Services in Kosovo - Demas, Angela; Aliu, Mrike; Coll-Black, Sarah; Zafeirakou, Aglaia; Hankey, Aline; Gotcheva, Boryana (World Bank, Washington, DC, 2021)
Low levels of foundational literacy and numeracy skills in Kosovo limit the ability of young adults to develop the skills required for the labor market and to lead full and productive lives. It is well documented that early childhood development (ECD)in the first 1,000 days of life lays the foundation for a lifetime of positive outcomes in health, education, wellbeing, and labor market productivity. This period is proven to be sensitive for brain development and strengthening of the immune system. The brain grows faster during this period than any other time. Children missing appropriate health and nutrition, education, and nurturing care supports in these critical years may encounter long-term difficulties in learning and life outcomes. Evidence finds that those who fall behind early struggle to catch up, losing out on valuable higher education and human capital potential. Research confirms that efforts and investments to improve human capital outcomes must start in the earliest years and employ a multisectoral approach to help children survive and thrive. The aim of this situational analysis is to support the government of Kosovo in developing a comprehensive strategy and enabling environment that support the equitable expansion of quality ECD services. This report analyzes multi-sectoral services supporting ECD in Kosovo by taking a child growth and development approach from pregnancy to entry to primary school, around six years old.